Pseudomonas piscium sp. nov., Pseudomonas pisciculturae sp. nov., Pseudomonas mucoides sp. nov. and Pseudomonas neuropathica sp. nov. isolated from rainbow trout. Issue 3 (25th March 2021) - Duman, Muhammed; Mulet, Magdalena; Altun, Soner; Saticioglu, Izzet Burcin; Gomila, Margarita; Lalucat, Jorge; Garcia-Valdes, Elena
Abstract : Six Gram negative, motile bacteria were isolated from rainbow trout ( Oncorhynchus mykiss ). The 16S rRNA sequence similarity values grouped them in the Pseudomonas mandelii (strains P49, P50 T, 154a T and P154b), Pseudomonas fluorescens (strain P115 T ) and Pseudomonas koreensis (strain P155 T ) phylogenetic subgroups in the genus Pseudomonas . The DNA G+C content ranged from 58.5 to 60 mol%. The strains were characterized phenotypically using API 20NE and Biolog GENIII tests, and chemotaxonomically by their whole-cell MALDI-TOF MS protein profiles and fatty acid contents. Multi-locus sequence analysis with four housekeeping gene sequences ( rpoD, rpoB, gyrB and 16S rRNA) together with genome comparisons by average nucleotide identity and genome-to-genome distance calculations were performed. Results showed that the similarity values of these strains to known species type strains were lower than the thresholds established for species in the genus Pseudomonas . Based on these data, we concluded that strains P49, P50 T, P115 T, P154a T, P154b and P155 T belonged to four novel species. The names proposed are: Pseudomonas piscium sp. nov. for strains P49 and P50 T with P50 T (=CECT 30175 T =CCUG 74871 T ) as the type strain; Pseudomonas pisciculturae sp. nov. for strain P115 T (CECT 30173 T =CCUG 74873 T ) ; Pseudomonas mucoides sp. nov. for strains P154a T and P154b with P154a T (=CECT 30177 T =CCUG 74874 T ) as the type strain; and Pseudomonas neuropathica sp. nov. for strain P155 T (=CECT 30178 T =CCUG 74875 T ).